Breast and cervical cancer risk in India: An update - Smita Asthana; Sonia Chauhan; Satyanarayana Labani (Wolters Kluwer Medknow Publications, 2014)
Background: Breast and cervical cancers are two major cancers among Indian women. Analysis of trends would help in planning and organization of programs for control of these cancers. Objective: The objective of the following study is to compute risk of breast and cervical cancers using updated data from different cancer registries of India and study of its trends. Materials and Methods: Data on incidence rates of breast and cervical cancers were obtained from six major cancer registries of India for the years 1982-2008 and from the recently initiated cancer registries, North Eastern Registries of India with a total of 21 registries. Annual percent change in incidence and risk in terms of one in number of women likely to develop cancer was estimated for both the cancers in various registries. Results: The annual percentage change in incidence ranged from 0.46 to 2.56 and −1.14 to −3.4 for breast and cervical cancers respectively. Trends were significant for both cancers in the registries of Chennai, Bangalore, Mumbai and Delhi except Barshi and Bhopal. North East region showed decrease in risk for breast and cervical cancers whereas increasing trend was observed in Imphal (West) and for cervical cancer in Silchar. Conclusion: North Eastern region recorded decline in the incidence of breast cancer which is contrary to the observation in other registries, which showed increase in breast cancer and decline in cervical cancer incidences.